Co-infection due to the hepatitis C virus and the human immunodeficiency virus in a population at risk - Odris Lescay Bell; Elba Patricia Cabezas Niubo; María Janine Suárez Suárez; Jesús Fernández Duharte; Daisy Martén Maren (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive, prospective and cross-sectional study of 25 patients with diagnosis of co-infection due to hepatitis C virus and that of the human immunodeficiency who had been referred to "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba, was carried out from January, 2012 to the same month in 2014, in order to determine the epidemiological, clinical and humoral characteristics in them.  In the series it was obtained that the infection due to both viruses was more frequent in the 30-39 age group (36.0%), in male sex (96.0%) and in the members of the multiple risks group (64.0%). Most of the patients had been diagnosed with the co-infection in less than the 3 years, they stated more than one clinical feature and presented high results in the liver functional tests.